METODE MERKLE HELLMAN UNTUK ENKRIPSI DAN DEKRIPSI PESAN WHATAPP - Leman, Dedi; Rahman, Maulia (Riau Journal Of Computer Science, 2020)
Encryption is a method of changing message data (plaintext) into password data (ciphertext), while decryption is a method of converting ciphertext to plaintext. WhatsApp Messenger is a messaging application for smartphones that is basically similar to BlackBerry Messenger. The WhatsApp Messenger application uses a 3G, 4G or WiFi internet connection for data communication. By using WhatsApp, we can do online chat, share files, exchange photos and so on. The algorithm used is 2 (two) types, namely symmetric algorithms and asymmetries algorithms. Merkle-Hellman Knapsack is a cryptosystem that uses the asymmetries algorithm. The Merkle-Hellman Knapsack implementation used uses xor logic. The key length is used between 8 to 72 bits. This capability makes Merkle-Hellman Knapsack have strong security with a short key length. Whereas the aim to be achieved is to apply the Merkman-Hellman Knapsack cryptosystem using the Visual Studio 2010 Programming Language